Investigation of a linear evolution system in the Banach space with random times of perturbations - Svishchuk, M. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a linear evolution system given in the Banach space and characterized by pulse perturbations at random times, we establish conditions for the existence of a unique solution of the Cauchy problem and investigate the stability of the zero solution.